“Experiência Literária”: uma análise mediológica da caixinha da TAG - Ferreira, Júlia Martins (2024)
In this work, we aimed to answer the question: what is the 'literary experience' sold by TAG - Literary Experiences? TAG is a book club with two subscription modalities, TAG - curation and TAG - unpublished, which monthly sends its members a 'surprise' box containing a collectible book jacket, an exclusive edition book, a magazine, a bookmark, and a literary gift. As a methodology of analysis, we consider this monthly sent box as a medium (DEBRAY, 1993; 2000), that is, a technical object mediating institutional and subjective relationships that in its double body, organized matter (OM) and materialized organization (MO), allows us to articulate three levels of analysis: the material, the diachronic, and the political. At the material level, we understand the objects that compose the box as editorial objects (SALGADO, 2020) organized by signifying values that lead to public circulation and project a reading public, that is, they are vectors of sensitivity (MO) pointing to a sociability matrix (OM). To discuss how the political and diachronic levels materialize in the sent box, we use the concepts of literary discourse (MAINGUENEAU, 2018a), technical-scientific-informational environment (SANTOS, 2013, 2006a, 2006b), and society of control (HAN, 2020; 2019; 2015 & SILVEIRA, 2018). Analyzing our object from the perspective of literary discourse allows us to describe the strategies that the company uses to position and validate itself in the literary field. Moreover, we could describe the textual scenography on the website and in the editorials of the sent magazines and the ethos that emerge from there, pointing to the same values: convenience, proximity, and performance. Ethos characteristic of digital media (SALGADO, 2021) that, supported by the Promethean tradition (MARTINS, 2012), make the 'literary experience' reach the members as a fable: 'a way to read more and better'. Framing our object in the context of the technical-scientific-informational environment allowed us to analyze how the characteristics of this environment also permeate the construction of meaning of the 'literary experience'. We understand that sending the same book with the same design and with a magazine containing a step-by-step guide to enjoy the 'monthly experience' homogenizes the relationship of the members with the reading of the sent book and with the 'literary experience' itself. In this sense, we intend to demonstrate through the description of the October 2022 and February 2023 boxes that this 'experience' acts as a verticality to its members, imposing a reading rhythm (one book per month) and controlling their perceptions and interpretations of both the book's story and what the 'literary experience' is. Thus, we describe in this work how the objects that compose the box sent by TAG (MO) constitute what the 'literary experience' is (OM) and how the 'literary experience' (OM) organizes the objects that compose the box sent by TAG (MO)."